The measurement, tracking and development practices of English professional football academies - Layton, M.; Taylor, J.; Collins, D. (Journal of Sports Sciences, 2023)
Tracking and measuring elements of performance is a well-established feature of practice in football academies. Player characteristics are considered, tracked, and measured using a variety of methods, with curricula often devised based on perceived importance and data interpretation. Against this breadth, our aim was to investigate the policies and systems in place at category one and two English football academies. Specifically, our objectives were (a) to understand what factors academies believe are important in the development of their players, (b) explore what academies are tracking and how they measure performance, and (c) analyse the extent to which these factors are integrated into the player`s curricula. A total of 15 participants with over 10 years` experience across 40 Talent Development (TD) environments were recruited to participate in semi-structured interviews. Using Reflexive Thematic Analysis (RTA), generated themes suggest that academies perceive a differential weighting between performance factors, with greatest importance placed on technical, tactical and psychological factors. A lack of clear measurement systematisation was often apparent. Finally, we identified methods of player curricula integration. We conclude by offering implications for academies to optimise integration of systems and processes that measure and track their players development.